Unemployment, Social Support, Individual Resources, and Job Search Behavior - Slebarska, K.; Moser, Klaus; Gunnesch-Luca, George (Journal of Employment Counseling, 2009)
The authors investigated the relation between the social support received by unemployed individuals (N = 104) and their job search behavior. A moderated mediation model demonstrated that the effect of social support on job search behaviors was mediated by self-esteem but only if adequacy of social support was perceived as low. In addition, the effect of social support on job search behavior was partially mediated by optimistic expectations and resilience. In sum, social support seems to be a resource with complex and partially surprising effects on job search behavior. © 2009 by the American Counseling Association. All rights reserved.
WiSo-Import:2015-03-26:416
Keywords: social support questionnaire; inventory of socially supportive behaviors; Transformation